2022
DOI: 10.1002/hyp.14575
|View full text |Cite
|
Sign up to set email alerts
|

Beyond fill and spill: Hydrological connectivity in a sub‐arctic bog‐fen‐tributary complex in the Hudson Bay Lowlands, Canada

Abstract: Patterned bog and fen peatlands, which dominate the landscape in the Hudson Bay Lowlands (HBL), act as important water storage and conveyance features in this region. In spite of their hydrological importance, there are currently no studies that define and characterize the thresholds of bog‐fen‐tributary hydrological connectivity in the HBL or their relation to seasonal and annual changes in water fluxes. To this end, hydrological (i.e., streamflow and groundwater levels) and meteorological (i.e., precipitatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 54 publications
0
3
0
Order By: Relevance
“…For example, McCarter and Price (2017) demonstrated a non‐stepwise expansion of contributing areas in a patterned fen with ridge‐flark microtopography, where ridge transmissivity increased exponentially as the water table rose into the upper 0.1 m of peat. Furthermore, Balliston and Price (2022) in a patterned bog‐fen complex showed that warmer‐than‐average springtime temperatures accelerated snowmelt faster than seasonal frost could sufficiently thaw in the fen, allowing snowmelt run‐off from the bog to short‐circuit and flow into the stream channel without replenishing fen storage. Consequently, during the summertime, hydrological connectivity was lower and threshold requirements were higher.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…For example, McCarter and Price (2017) demonstrated a non‐stepwise expansion of contributing areas in a patterned fen with ridge‐flark microtopography, where ridge transmissivity increased exponentially as the water table rose into the upper 0.1 m of peat. Furthermore, Balliston and Price (2022) in a patterned bog‐fen complex showed that warmer‐than‐average springtime temperatures accelerated snowmelt faster than seasonal frost could sufficiently thaw in the fen, allowing snowmelt run‐off from the bog to short‐circuit and flow into the stream channel without replenishing fen storage. Consequently, during the summertime, hydrological connectivity was lower and threshold requirements were higher.…”
Section: Discussionmentioning
confidence: 99%
“…rose into the upper 0.1 m of peat. Furthermore, Balliston and Price (2022) in a patterned bog-fen complex showed that warmer-thanaverage springtime temperatures accelerated snowmelt faster than seasonal frost could sufficiently thaw in the fen, allowing snowmelt run-off from the bog to short-circuit and flow into the stream channel without replenishing fen storage. Consequently, during the summertime, hydrological connectivity was lower and threshold requirements were higher.…”
Section: Apparent Hydrological Functionmentioning
confidence: 99%
See 1 more Smart Citation